Economic, Environmental, and Social Performance of SRIKEHATI’s Listed Companies. Does It Affect the Company's Profit? - Maleachi Eka Prasetya; Fanny Septina (LPPM Universitas BSI, 2023)
A good company is a company that is concerned with the economic aspects that benefit the company and prioritizes environmental and social aspects. This study aims to determine how much influence the sustainability report has on the company's financial performance in 2018-2021. This study uses a quantitative approach method. The population in this study is a company that has been registered in the Stock Index SRI-KEHATI because this company has implemented sustainable accounting on the company's financial statements. The sample used in this study is the SRI-KEHATI’s indexed companies which has published a Sustainability Report and an annual report. The results are that the Sustainability Report's disclosure in terms of economic performance has a significant negative effect on company profitability, environmental aspects has a significant positive effect on company profitability, and social aspects has no significant effect on company profitability. This can be a consideration for companies in implementing ESG issues by disclosing a Sustainability Report regarding their production operations even though the reporting is still voluntary. It is proven that the disclosure of economic and environmental aspects transparently can increase the company's profits.